The effect of psycho-education about_x000D_ maternal attitudes on childhood obsessive_x000D_ compulsive disorder symptoms_x000D_ compulsive disorder symptoms - (:unkn) unknown (My University, 2020)
investigate relationship between maternal attitudes andsubclinical childhood Obsessive Compulsive Disorder(OCD) in Turkish sample. Study also investigates theeffectiveness of 8-sessions psycho-education programabout maternal attitudes. Method: Sample consisted of97 mother-child pairs and children's age ranged between8 to 10. Parental Attitudes Research Instrument (PARI),Leyton Obsessional Inventory Child Version (LOI-CV),State-Trait Anxiety Inventory for Children (STAI-CH) andChildren’s Depression Inventory (CDI) were used asassessment tools. After initial assessments, fifteen mothersrandomly assigned either to group psycho-educationcondition (n=8) or waiting-list control condition(n=7). Results: Marital conflict was positively correlatedwith total interference score in LOI-CV, total score in LOICVand A-Trait anxiety symptoms (r=.23, r=.24 and r=.24, respectively). Authoritarianism positively correlatedwith A-Trait anxiety symptoms (r=.25). Findings alsoindicated that there was a statistically significant differencein total scores of negative attitudes (Z=-2.201,p=.028), and posttest scores of these variables showedsignificant decrease after psycho-education program.There were statistically significant change in interfere(Z=-2.371, p=.018) and total (Z=-2.366, p=.018) scoreof OCD symptoms after psycho-education program.Discussion: Marital conflict has a significant relationshipwith subclinical OCD symptoms. Marital conflict andauthoritarian attitude also have significant relationshipwith trait anxiety symptoms in children. Furthermore,psycho-education program was effective in reducingnegative maternal attitudes and children’s subclinicalOCD symptoms

Amaç: Çalışmanın öncelikli amacı Türk popülasyonunda_x000D_ anne tutumları ve çocukluk çağı eşik altı OKB belirtileri_x000D_ arasındaki ilişkiyi incelemektir. Çalışmada, anne tutumları_x000D_ ile ilgili 8 seanslık psiko-eğitim çalışmasının etkililiğinin_x000D_ de incelenmesi amaçlamıştır. Yöntem: Örneklem, 8-10_x000D_ yaş grubu çocuklar ve onların anneleri olmak üzere 97_x000D_ çocuk-anne çiftinden oluşmuştur. Aile Hayatı Çocuk_x000D_ Yetiştirme Tutum Ölçeği, Leyton Obsesyon EnvanteriÇocuk_x000D_ Formu, Durumluk/Sürekli Kaygı Envanteri-Çocuk_x000D_ Formu ve Çocuklar için Depresyon Ölçeği ölçüm araçları_x000D_ olarak kullanılmıştır. İlk ölçümlerin ardından, 15 anne_x000D_ seçkisiz atama yöntemi ile psiko-eğitim (n=8) ve bekleme_x000D_ listesi-kontrol gruplarına (n=7) atanmıştır._x000D_ Bulgular: Evlilik çatışması ve OKB semptomlarının_x000D_ şiddeti, OKB semptomları, ve sürekli kaygı semptomları,_x000D_ arasında pozitif yönde anlamlı ilişki saptanmıştır_x000D_ (sırasıyla, r=.23, r=.24 ve r=.24). Otoriter tutum ise_x000D_ sürekli kaygı belirtileri ile pozitif yönde anlamlı biçimde_x000D_ ilişkilidir (r=.25). Bulgular ayrıca, annelerin negatif_x000D_ tutumlarında (Z=-2.201, p=.028) istatistiksel olarak_x000D_ anlamlı değişim görüldüğünü ve son test ölçümlerinde_x000D_ anlamlı düzeyde azalmanın olduğunu göstermektedir._x000D_ Psiko-eğitim sonrası OKB semptomları (Z=-2.366,_x000D_ p=.018) ve semptomların şiddetinde (Z=-2.371,_x000D_ p=.018) anlamlı değişim saptanmıştır. Sonuç: Evlilik_x000D_ çatışması, eşik altı OKB semptomlarıyla anlamlı derecede_x000D_ ilişkilidir. Evlilik çatışması ve otoriter tutum, sürekli kaygı_x000D_ belirtileriyle anlamlı derecede ilişkilidir. 8 haftalık psikoeğitim_x000D_ programının hem annelerin olumsuz tutumlarını_x000D_ hem de çocuklarda görülen eşik altı OKB semptomlarını_x000D_ azaltıcı etki gösterdiğini saptanmıştır
Anne tutumlarına yönelik psikoeğitimin çocukluk çağı obsesif kompulsif bozukluk semptomlarına etkisi